Risk factors in the transmission and seroprevalence of Chlamydophila abortus infection in sheep and goats - Leopoldo, Tadeu Bezerra; Pinheiro, Raymundo Rizaldo; Alves, Francisco Selmo Fernandes; Porfirio, Kenney de Paiva; Rêgo, Wagner Martins Fontes do; Diniz, Bruno Leandro Maranhão; Cardoso, Janaina de Fátima Saraiva; Paula, Ney Rômulo de Oliveira (Pesquisa Agropecuaria Brasileira, 2016)
The objective of this work was to evaluate the risk factors involved in the transmission of Chlamydophila abortus to sheep and goats, as well as to verify the seroprevalence of the infection. One hundred ten farms were selected, with a total of 500 sheep samples – 350 from the Microregion of Alto Médio Gurgueia (MRAMG), and 150 from the Homogeneous Microregion of Teresina (MRHT), both in the state of Piauí, Brazil – and 600 goat samples – 300 of the MRAMG and 300 of the MRHT. An epidemiological questionnaire was used to identify the main risk factors. Anti‑C. abortus antibodies were detected by the complement fixation technique. Overall prevalence of infection by C. abortus was 7.2% (79/1,100). The prevalence in goats and sheep in the MRAMG was 7.9% (51/650), and in the MRHT it was 6.2% (28/450). In the studied microregions, the prevalence in sheep was 8.2% (41/500), and in goats it was 6.3% (38/600). The raising system, reproductive practices, and racial type were significant risk factors for infection in sheep. Also significant in goats were the reproductive practices and the origin of the does and bucks. The Dorper breed shows increased susceptibility to infection with C. abortus.